The role of the RFID polarization mismatch in the Simultaneous Localization and Mapping problem - Giampaolo, Emidio Di; Martinelli, Francesco; Romanelli, Fabrizio (IEEE journal of radio frequency identification (Online), 2023)
Several localization algorithms exploit the dependence of the phase shift of the backscattered RFID signal on the tag to the reader distance. However, in some configuration setups, the phase shift also depends on the relative orientation between the tag's and the reader's antenna. In this paper we investigate the effects of this dependence on the Simultaneous Localization and Mapping (SLAM) problem, by comparing the approach where this dependence is included in the measurement model with the approach where it is rather compensated through a time varying phase offset subject to estimation. Simulation and experimental results show that the algorithm which includes this dependence in the measurement model provides better performances with respect to the other approach. Some indications and numerical results are also reported in the paper to evaluate if this dependence may be beneficial in solving the SLAM problem.